Inhibition Properties and Thermodynamic Changes of Binding of p-perazine-bis and p-peridine Dithiocarbamate Sodium Salts to Mushroom Tyrosinase - Ehsan Amin; Ali Akbar Saboury; Hassan Mansouri-Torshizi; Samaneh Zolghadri (Iranian Journal of Chemistry & Chemical Engineering, 2019)
A mono- and a bi-functional dithiocarbamates as sodium salts were obtained by treating p-peridine or p-perazine in aceton-water mixture with CS2 in the presence of NaOH. These anionic water soluble compounds have been characterized by elemental analysis, IR and 1H NMR spectroscopic studies. Both compounds (p-peridine (I) and p-perazine-bis dithiocarbamate (II) sodium salts) were examined for inhibition of mushroom tyrosinase (MT) activity. The results showed that they inhibit MT competitively. KI values of two compounds at 27°C are 2 and 4 mM. Therefore, the compound (I) is more potent than (II). They chelate active site of tyrosinase via electrostatic interactions. These conclusions are proved by obtained thermodynamic parameters and fluorescence studies. Extrinsic fluorescence studies disprove any tertiary structure changes of MT. Major enthalpy changes in binding of compound (II) in comparison to (I) show that including two carbamate tails in such compounds disturb balancing of hydrophobic interactions with vicinity of active site of enzyme.